The changeability of Shari`ah rulings: an analysis of the contemporary discourse - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas (The University of Chitral, 2021)
Shari`ah and its practical legal rules primarily are of divine origin according to Muslims` belief. Nevertheless, the revealed nature of the Shari`ah does not imply that it is a static system incapable of providing solutions to changing human situations due to change in time and space. It takes cognizance of such changing needs of humans primarily in two ways: at the level of its textual laws, it takes into account the time-space requirement of their applicability on people, and at the event of unfolding new situations and novelties of human life, it mandates ijtihad to resolve them. At the age of globalization, however, this unique feature of Divinebased system of stable but flexible Shari`ah has become a mooting point among some segments who would like to go ultra-realists either mala fide or out of naïve notion of defending time-space suitability of the Shari`ah even if it is at the expense of disbanding its divinely fixed legal corpus. Accordingly, this paper argues that a methodological analysis of the principles of changing the Shari`ah rulings on account of changing circumstances do not allow for laissez-fair and arbitrary alteration of the fixed structure and essence of the Shari`ah.